Description of knowledge and Attitudes Breast Self-Examination (BSE) in Women of Fertile Age in the Kalumbuk District - Yulizawati Yulizawati; Hardisman Hardisman; Filda Filda (Journal of Midwifery, 2020)
Breast cancer (Ca Mamae)  is a major health problem in Indonesia and the world. One of the causes of this disease can’t be cured when found in the advanced stage.  The efforts of preventing and controlling breast cancer by the government have been conducted by the clinical Breast Examination (CBE). CBE is done by medical personnel. CBE formed women to be able to perform breast self-examination (CBE). CBE is an early detection intervention that has many advantages including simple, easy and practical. If done correctly and periodically can detect early breast cancer. The purpose of this research is to look at the knowledge and attitude of CBE in women of childbearing age (WUS) in Kalumbuk District.MethodThis type of research uses quantitative descriptive with simple random sampling. Data suspension was conducted on October 2019 – July 2020. The population of this research is 30-50 years old in women of fertile age. The number of samples in this study was 101 respondents. Data processing using   SPSS 25 software.ResultsThe results of the study gained that the knowledge of respondents in the category is sufficient, while the respondents attitude is in the negative attitude category to BSE.ConclusionKnowledge is enough and the negative attitude to BSE this is being done by a number of things such as age, education, employment, and health education BSE.